The protective effects of S14G-humanin (HNG) against lipopolysaccharide (LPS)- induced inflammatory response in human dental pulp cells (hDPCs) mediated by the TLR4/MyD88/NF-κB pathway. Issue 1 (1st January 2021) - Zhang, Ping; Cui, Zhiqiang; Li, Shuai
ABSTRACT: Pulpitis is reported in large populations of patients and significantly impacts their normal life quality. It is reported that the lipopolysaccharide (LPS) in Gram-negative bacteria induces severe inflammation in dental pulp tissues. S14G-humanin is a derivative of humanin and has been recently confirmed to possess promising anti-inflammatory properties. The current study aims to explore the possibility of treating pulpitis with S14G-humanin. LPS-stimulated dental pulp cells (DPCs) were utilized to simulate an inflammatory state in the progression of pulpitis. We found the elevated expressions and production of interleukin- 6 (IL-6), tumor necrosis factor-α (TNF-α), macrophage chemoattractant protein-1 (MCP-1), matrix metalloproteinase-2 (MMP-2), and matrix metalloproteinase-9 (MMP-9), upregulated Pentraxin 3 (PTX3) and activated oxidative stress in LPS-treated DPCs were all reversed by treatment with 50 and 100 μM S14G-humanin. In addition, the LPS-induced elevated expression levels of toll-like receptor 4 (TLR4) and myeloid differentiation primary response 88 (Myd88), and activation of the IκBα/NF-κB signaling pathway in hDPCs were significantly repressed by treatment with S14G-humanin. Conclusively, we found that S14G-humanin protected LPS-treated hDPCs by inhibiting the TLR4/MyD88/NF-κB signaling pathway.